2018
DOI: 10.7748/nm.2018.e1674
|View full text |Cite
|
Sign up to set email alerts
|

Simulation using ‘live’ adult service users and moulage in a variety of settings

Abstract: This article shows how simulation can be modified and adapted to benefit higher education institutions (HEIs) in a variety of situations. These situations can involve the engagement of service users (SUs) and moulage, or application of make-up to simulate clinical presentations, to ensure skill enhancement, ultimately to support and empower students so they can achieve their potential. This article describes a unique collaboration between staff at an HEI and SUs, who have worked together in simulation activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…15,24,25 Perhaps this represents a perception that SBE should focus on those skills and experiences that are most challenging to experience in clinical placement, yet many papers have reported great value in engaging service users in SBE. 20,26 Alternatively this may represent the logistical challenges presented by COVID-19 restrictions in terms of accessing these individuals.…”
Section: Sbe Resources and Activitiesmentioning
confidence: 99%
“…15,24,25 Perhaps this represents a perception that SBE should focus on those skills and experiences that are most challenging to experience in clinical placement, yet many papers have reported great value in engaging service users in SBE. 20,26 Alternatively this may represent the logistical challenges presented by COVID-19 restrictions in terms of accessing these individuals.…”
Section: Sbe Resources and Activitiesmentioning
confidence: 99%
“…On reflecting on their experiences of the quality of the IPWS activity, the SPs in this study highlighted the importance of feeling prepared in their role, being aware of what to expect from students, and desire to be more involved in feedback to students. Preparation in a simulation role has previously been discussed by Edwards and McCormack 16 where SPs identified that their own preparation was important, with requests for more development to improve confidence, engagement, and clarification on their role in providing feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The design included the capstone assessments, self-reflection and peer review, student and staff preparation and moulage, or casualty make-up for training purposes that allows actors to appear older or to have wounds (Edwards and McCormack 2018), for authenticity.…”
Section: Designmentioning
confidence: 99%